Innovation, Productivity and Economic Development in Latin America and the Caribbean - Daude, Christian (OECD Publishing, 2010)
GDP per capita in Latin America has been falling behind high-income countries and other benchmarks for decades and the region's mediocre growth performance is one of the main reasons why poverty reduction, and living standards more generally, in the region is well below that observed in peer countries. In this paper, we explore some of the potential roots of this poor performance by using development accounting techniques. The results point towards total factor productivity as the main culprit for the region's lack of convergence. In order to investigate what causes the lack of productivity catch-up, we analyse the determinants of technology diffusion, in particular of internet and mobile phone technologies. The empirical results show that institutions, absorption capacity (human capital), and financial constraints are the main explanatory variables of the diffusion gaps in these technologies between the OECD and Latin America. We also explore the performance of the region in terms of health outcomes, reflected in the evolution of life expectancy, and the specific role played by technological innovation and adoption. Finally, a calibration exercise of an endogenous growth model allows us to assess the extent to which the region's per capita income gap is due to problems in factor accumulation or distortions that reduce the incentives to innovate; the results point to very different situations across countries in the region. While for some countries we find evidence of ,innovation shortfalls?, other countries' problems concentrate around low factor accumulation
Keywords: Development